Advanced control for multi-area power system incorporating renewable energy sources and energy storage systems - Bishoyi Aswini Kumar (Nanyang Technological University, 2023)
It is too ambitious, but renewables could supply four-fifths of the world’s electricity by 2050, massively cutting emissions and helping to mitigate climate change. This transformation of the global energy system to reduce greenhouse emissions requires engagement at all levels. In a feasible energy future, mass inclusion of alternate energy (Wind, Tidal) into the grid will play a viable role in the transformation.